Acceptability of Home‐Based Chlamydia And Gonorrhea Testing Among a National Sample Of Sexual Minority Young Adults. Issue 1 (March 2015) - McRee, Annie‐Laurie; Esber, Allahna; Reiter, Paul L.
Abstract : CONTEXT: STDs are common among older adolescents and young adults; hence, STD screening is a public health priority. Home‐based STD testing could be a strategy to improve screening rates, particularly among at‐risk populations, including sexual minority (i.e., nonheterosexual) young adults. METHODS: Data were collected from a national sample of 971 sexual minority young adults aged 18–26 through an online survey in the fall of 2013. Logistic regression analyses identified associations between respondents' characteristics and their willingness to use a home‐based test for chlamydia and gonorrhea. RESULTS: A greater proportion of men than of women were willing to use a home‐based STD test (81% vs. 68%). Willingness was more likely among gay than among bisexual men, among men insured through their parents than among the uninsured and among those who had had two or more sexual partners in the past year than among those who had had fewer (adjusted odds ratios, 2.0–2.2). Among men, students were less likely than the employed to report willingness for home‐based testing (0.4). Among women, willingness was more likely among those who reported at least two partners in the past year than among those who reported fewer (1.6). Overall, respondents' most common concerns about home‐based STD testing regarded test accuracy, their ability to do the test correctly and their preference to see a doctor for testing. CONCLUSIONS: Home‐based STD testing may be a promising strategy for screening sexual minority young adults; understanding correlates of willingness and young adults' concerns may help inform self‐testing programs.